Analisis Kontrastif Konsep Verba Dan Nomina Verba Dalam Nahwu Basrah Dan Kufah - Astari, Rika (LISANIA Jurnal Ilmu dan Pendidikan Bahasa Arab, 2011)
The aim of this research is to explore the concept of verb and verbal noun according to Basrah and Kufah schools of nahwu, and then to reveal differences and similarities of the concepts within Arabic Language in accordance to both schools. The research data consist of principle rules in nahwu of Basrah and Kufah which are selected from the book entitled al-Insaf fi Masail al-Khilaf. So, the source of primary data in the research is sort of the written ones. The method used for analyzing data is distribution method in which determination instrument is taken from the language itselfÂ  with basic technique of elements direct distribution. The result concludes that differences of verb and verbal noun conceptÂ  are that derivations of active participle (ism faâil), passive participle (isim maful), nomina loci et temporaris (ism makan wa ism zaman), and instrumental noun (ism alat) are based on verb and not from verbal noun. There are many stipulations required before functionalization of verbal noun, the subject of verbal noun may be elided in contrast with the subject of verb when being elided will cause multi-meaning. The meanings included in verb are more various than that in verbal noun. Conjugations take place in verb in its perfect, imperfect and imperative forms while verbal noun has no conjugation. Whereas some similarities found are that verb has time meaning and generality is needed in using it as well as verbal noun. Keywords: Verba, Verbal Noun, nahwu Basrah, nahwu Kufuh